KONSELING MENGGUNAKAN LEMBAR BALIK UNTUK MENINGKATKAN PENGETAHUAN, SIKAP DAN PERILAKU IBU MELAKUKAN PENYAPIHAN DENGAN METODE BABY LED WEANING DI PUSKESMAS PUGER - Agustin, Elok Silvia; Fitrianingtyas, Rizki (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2025)
The weaning period is a period when the child's dependence on breast milk from his mother is severed. Weaning in the wrong way, as is often done by society, has a negative impact in terms of health such as children becoming fussy, aggressive, poisoned and traumatized. The purpose of this service is to provide information about proper weaning to mothers at the Puger Health Center. The service method is carried out by providing counseling. This community service has been carried out on February 3 - 22, 2024. Precisely in the Puger Health Center area. The target of this activity is mothers who have children aged 19-24 months as many as 54 respondents. The results of the service showed that of the 54 respondents before the counseling, most of them had the criteria of lack of knowledge (56%), poor attitude (55%), poor behavior (52%) and after being given counseling most of the respondents had sufficient knowledge (48%), good attitude (59%), good behavior (72%). The conclusion is that Giving information